Design and Control System of VTOL Drone Bom Carrier - Ardiansyah, Ardiansyah; Pratisna , Pompy; Hidayat, Sutikno Wahyu; Ghofur , Ahmad Ainul (Journal of Industrial Engineering & Management Research, 2026)
This study presents the development of a Vertical Take-Off and Landing (VTOL) drone system capable of autonomously carrying and releasing a lightweight bomb payload with high precision. The drone employs a hybrid quadcopter–fixed-wing configuration, using the Speedybee F405 flight controller with ArduPilot firmware, supported by GPS, IMU, and barometer sensors for autonomous navigation. Testing was conducted through Software-In-The-Loop (SITL) simulation and limited field trials. Results demonstrate stable hovering with a position deviation of less than ±0.5 meters, waypoint navigation accuracy of ±1.2 meters, and a payload release success rate of 75%. The system shows strong potential for further development as a tactical UAV platform with semi-autonomous and high-precision operational capabilities.